Genotyping low-grade gliomas among Hispanics (2016)
Low-grade gliomas (LGGs) are classified by the World Health Organization as astrocytoma (DA), oligodendroglioma (OD), and mixed oligoastrocytoma (OA). TP53 mutation and 1p19q codeletion are the most-commonly documented molecular abnormalities. Isocitrate dehydrogenase (IDH) 1/2 mutations are frequent in LGGs; however, IDH-negative gliomas can also occur. Recent research suggests that ATRX plays a significant role in gliomagenesis. We investigated p53 and Olig2 protein expression, and MGMT promoter methylation, 1p19q codeletion, IDH, and ATRX status in 63 Colombian patients with LGG. The overall survival (OS) rate was estimated and compared according to genotype. The most common histology was DA, followed by OD and OA. IDH1/2 mutations were found in 57.1% and MGMT+ (positive status of MGMT promoter methylation methyl-guanyl-methyl-transferase gene) in 65.1% of patients, while overexpression of p53 and Olig2 was present in 30.2% and 44.4%, respectively, and 1p19q codeletion in 34.9% of the patients. Overexpression of ATRX was analyzed in 25 patients, 16% tested positive and were also mutations in isocitrate dehydrogenase and negative 1p19q-codelition. The median follow-up was 15.8 months (95% CI, 7.6–42.0) and OS was 39.2 months (95% CI, 1.3–114). OS was positively and significantly affected by MGMT+, 1p19q codeletion, surgical intervention extent, and number of lobes involved. Multivariate analysis confirmed that MGMT methylation status and 1p19q codeletion affected OS. This is the first study evaluating the molecular profile of Hispanic LGG patients. Findings confirmed the prognostic relevance of MGMT methylation and 1p19q codeletion, but do not support IDH1/2 mutation as a relevant marker. The latter may be explained by sample size and selection bias. ATRX alterations were limited to patients with DA and were mutations in isocitrate dehydrogenase and negative 1p19q-codelition.